2006
DOI: 10.1111/j.1365-2893.2006.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation and comparison of indexes for fibrosis and cirrhosis prediction in chronic hepatitis C patients: proposal for a pragmatic approach classification without liver biopsies

Abstract: Noninvasive indexes have been developed to predict fibrosis staging. The aim of this study was to assess the diagnostic accuracy of these indexes in comparison with liver histology in hepatitis C virus (HCV)-infected patients. A total of 235 consecutive patients with HCV infection from the Fibropaca multicentre independent study were included in this paper. FibroTest (FT), aspartate aminotransferase to platelet ratio index (APRI) and Forns score were assessed in the cohort and compared with liver histology per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
3
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 19 publications
7
89
3
5
Order By: Relevance
“…These results have been confirmed in a large-scale, multicenter international validation study of more than 2,000 patients with chronic hepatitis C [110]. Other groups have proposed alternative algorithms combining FibroTest Ò and APRI [53] either with Forns index (Fibropaca) [111] or Hepascore [112].…”
Section: Comparison and Combination Of Approachesmentioning
confidence: 72%
“…These results have been confirmed in a large-scale, multicenter international validation study of more than 2,000 patients with chronic hepatitis C [110]. Other groups have proposed alternative algorithms combining FibroTest Ò and APRI [53] either with Forns index (Fibropaca) [111] or Hepascore [112].…”
Section: Comparison and Combination Of Approachesmentioning
confidence: 72%
“…More recently, Bourlière et al 26 showed that the combination of the APRI test, FibroTest, and Forns score in HCV-monoinfected patients allowed 191 of 235 (81.3%) patients to be correctly classified, thus avoiding LB. The FIB-4 index is a new noninvasive test for the assessment of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A SAFE biopszia pontossága 90% volt szignifi káns fi brosis, és 93% cirrhosis esetében, a biopsziák 45-82%-a volt elkerülhető. Egy másik munkacsoport által összeállított Fibropaca algoritmus (Fibrotest-Fibrosure, APRI és/vagy Forns index) pontossága 81,3% volt, a biopsziák 81,3%-a volt elkerülhető [34]. A Fibrotest és APRI alkalmazásával létrehozott Leroy's algoritmus pozitív és negatív prediktív értéke körülbelül 95% [35], de nem volt reprodukálható [14].…”
Section: Szérum-fi Brosismarkereket Kombináló Algoritmusokunclassified